SUT Sucrose and MST Monosaccharide Transporter Inventory of the Selaginella Genome - Lalonde, Sylvie; Frommer, Wolf B. (Frontiers in Plant Science, 2012)
While most metazoa mainly use hexose transporters to acquire hexoses from their diet and as a transport form for distributing carbon and energy within their bodies, insects use trehalose and plants use sucrose as their major form for translocation. Plant genomes contain at least three families of mono- and disaccharide transporters: monosaccharide/polyol transporters that are evolutionary closely related to the yeast and human glucose transporters, sucrose transporters of the SUT family, which similar to the hexose transporters belong to the major facilitator superfamily (MFS), but share only minimal amino acid sequence homology to the hexose transporters, and the family of SWEET sugar transporters conserved between animals and plants. Recently, the genome sequence of the spikemoss Selaginella has been determined. In order to study the evolution of sugar transport in plants, we carried out a careful annotation of the complement of sugar transporters in Selaginella. We review what is known about sugar transport in spikemoss and provide phylogenetic analyses of the complement of MST and SUT homologs in Selaginella.